Level of Likeability and Fiber Content in Non-gluten Cookies with Subtitution of Banana Flour and Addition of Basil Seeds - Aidiyah Fitri; Noor Rohmah Mayasari (Jurnal Gizi dan Kesehatan Nusantara, 2025)
Background: This study was motivated by the growing trend in gluten-free product consumption, which has shown a significant increase in recent years both in Indonesia and globally, as well as the generally low dietary fiber intake among the population. These conditions have driven the need for innovative product development that caters to gluten-intolerant individuals, such as high-fiber non-gluten cookies. Purpose: The research aims to determine the level of likebility and fiber content in non-gluten cookies formulated with banana flour substitution and basil seed addition. Methods: A factorial completely randomized design (CRD) was used with three levels of substitution: 80% cornstarch : 20% banana flour, 60% cornstarch : 40% banana flour, and 40% cornstarch : 60% banana flour, as well as three levels of basil seed addition (2.5%, 5%, and 7.5%). Organoleptic tests were conducted with 30 untrained panelists, while dietary fiber analysis was carried out on the best product formulation. Result: The results showed that the formulation of 80% cornstarch : 20% banana flour with 7.5% basil seed addition was the most preferred product. The dietary fiber content of the best formulation was 7.88% ± 0.04. Conclusion: The conclusion of this study is that the substitution of banana flour and the addition of basil seeds can increase dietary fiber content and are organoleptically acceptable to consumers. The fiber content of the best product falls into the high-fiber category.